FUNCTIONALIZATION OF THE USE OF ENGLISH FOR TOUR GUIDE IN OKDO TOUR & TRAVEL MEDAN - Bima Prana Chitra; Misla Geubrina; Hendra Mulia (JURNAL EDUCATION AND DEVELOPMENT, 2024)
English plays an important role in the tourism industry, especially in promoting overseas tours through tour guides. The communication that occurs between tour guides and tourists is related to the image of Indonesia by these tourists. By mastering foreign languages, as well as understanding the culture of various countries, it is expected to be able to provide the best service and be able to create a good impression or image which has the effect of increasing the Indonesian tourism industry. So in this study, functionalization of the use of English is needed so that the English language is easy to understand in order to the message conveyed by the speaker can be easily understood by the listener, especially for tour guides at Okdo Tour & Travel. The method used in this study is qualitative and data obtained through observation. Based on the research, it can be concluded that the tour guides lack of interest in honing English skills so that it affects the development of the potential that exists within the tour guides and it requires more professional English tutors so they can learn and use English in various activities.